2008
DOI: 10.15288/jsad.2008.69.866
|View full text |Cite
|
Sign up to set email alerts
|

Three-Year Changes in Adult Risk Drinking Behavior in Relation to the Course of Alcohol-Use Disorders

Abstract: ABSTRACT. Objective: This study examines the associations between the course of alcohol-use disorder (AUD) and changes in average daily volume of ethanol intake, frequency of risk drinking, and maximum quantity of drinks consumed per day over a 3-year follow-up interval in a sample of U.S. adults. Method: Data were taken from a longitudinal study of a nationally representative sample of U.S. adults, who were 18 years of age and older (mean age = 46.4) when initially interviewed in 2001-2002 and successfully re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 65 publications
(66 reference statements)
5
32
1
Order By: Relevance
“…This study lacked a gold standard measure for alcohol misuse. However, the rates of conversion from a negative to a positive screen in this study correspond with the rates of low-risk drinkers converting to problematic alcohol use (e.g., meeting criteria for alcohol use disorders) ascertained through rigorous interviews (Dawson et al, 2008). As above, some positive screens at follow-up were likely false positives, and some initial negative screens were likely false negatives, and prevalence of these screens needs to be investigated (Bradley et al, 2011b).…”
Section: Discussionsupporting
confidence: 55%
“…This study lacked a gold standard measure for alcohol misuse. However, the rates of conversion from a negative to a positive screen in this study correspond with the rates of low-risk drinkers converting to problematic alcohol use (e.g., meeting criteria for alcohol use disorders) ascertained through rigorous interviews (Dawson et al, 2008). As above, some positive screens at follow-up were likely false positives, and some initial negative screens were likely false negatives, and prevalence of these screens needs to be investigated (Bradley et al, 2011b).…”
Section: Discussionsupporting
confidence: 55%
“…Specifically, longitudinal epidemiological studies generally observe high remission rates of AUDs (de Bruijn et al, 2006), whereas clinical studies describe AUD as a chronic relapsing disorder (Storbj€ ork and Room, 2008). Perhaps, the higher rate of excessive drinking among those with AUD in clinical research compared with those in epidemiological research could play a role in this discrepancy (Dawson et al, 2008;Storbj€ ork and Room, 2008). Specifically, AUDs with excessive drinking may be associated with more persistency than AUDs without excessive drinking.…”
Section: Discussionmentioning
confidence: 99%
“…Nationally representative and longitudinal studies generally have observed drinking patterns for less than 5 years (Dawson et al, 2008;Karlamangla et al, 2006;Perreira and Sloan, 2001) or fewer than fi ve interviews (Goodwin et al, 1987;Moore et al, 2005;Perreira and Sloan, 2001). Longitudinal studies examining relationships between drinking behavior and age have offered limited insight into correlates of changes in drinking other than for demographic factors.…”
Section: H Igh Levels Of Alcohol Consumption Bymentioning
confidence: 99%